Cybersecurity and international collaboration in STEM: The role of global partnerships in protecting digital infrastructures and data - Gole, Ricky; Paudel, Roshan (American Journal of STEM Education, 2026)
International partnerships are now essential for securing digital infrastructures and data in STEM research, yet these collaborations also increase the complexity of cybersecurity risk management. This study systematically reviews recent literature and policy initiatives to evaluate how global alliances address cybersecurity challenges in collaborative STEM environments. Our analysis of 43 core studies reveals that effective partnerships drive the development of joint security frameworks, facilitate the sharing of threat intelligence, and support the harmonization of data governance across jurisdictions. The results show that while disparities in technical capacity and regulatory alignment persist, international initiatives such as the G7 Research Security Working Group and UK–US–Canada research alliances play pivotal roles in strengthening resilience against sophisticated cyber threats.